KANTAS IR DELEUZE’AS: KOKIA YRA GILIAUSIA VAIZDUOTĖS PASLAPTIS? - Baranova, Jūratė (Problemos, 2013)
Straipsnyje nagrinėjama Kanto nužymėtos ir Deleuze’o eksperimentiniame mąstyme rekonstruotos vaizduotės kaip vieno iš trijų proto gebėjimų raiškos lauko alternatyvos. Siekiama atsakyti į paties Deleuze’o išsikeltą kantišką klausimą: kokia yra giliausia paslaptis? Aptinkamos kelios atsakymo alternatyvos. Šiame tyrime paaiškėjo, kad Deleuze’o atsakymai į paties išsikeltą klausimą „kokia yra giliausia vaizduotės paslaptis?“ patiria metamorfozes, kurios apsuka ratą. Nuo pradinės pozicijos, kai vaizduotė veikia tik paklusdama intelektui ar protui, ji juda link laisvo trijų nepriklausomų sugebėjimų – intelekto, proto, vaizduotės atitikimo, paskui – link jų nedarnios dermės, jų kovos, kuri skatina kiekvienos naują atsiskleidimą, galiausiai – prie vaizduotės anihiliacijos, kuri leidžia užgimti naujai minčiai, taigi, ratas apsisuka ir grįžtama prie jų dermės naujame lygmenyje, moderuojant filosofiniam skoniui. Tačiau visas šias metaformorfozes jungia viena bendra Kanto suformuluota prielaida: vaizduotė niekada neišvengia triadinės priklausomybės, ji neveikia viena; ji galima tik santykyje su intelektu ir protu, t. y. kitais trimis jai paraleliais ir simultaniškais sugebėjimais.Pagrindiniai žodžiai: Kantas, Deleuze’as, vaizduotėKant and Deleuze: What is the Deepest Secret of Imagination? Jūratė BaranovaAbstract The paper discusses the problem of possible philosophical understanding of imagination from the Kantian-Deleuzean point of view. At the begining of his philosophical carreer, one can say, “early Deleuze” in 1963 published the book „Kant’s Critical Philosophy“ (La philosophie critique de Kant). The same year he wrote an essay “The Idea of Genesis in Kant’s Esthetics”. In both texts returning to Kant’s book Critique of Pure Reason, Deleuze notices, that it is widely acknowledged that schematizing is an original and irreducible act of imagination: only imagination can and knows how to schematize. Nevertheless, the imagination does not schematize of its own accord, simply because it is free to do so. It schematizes only for a speculative purpose, in accordance with the determinate concepts of the understanding; when the understanding itself plays the role of legislator. This is why it would be misguided to search the mistery of schematizing for the last word on the imagination in its essence or in its free spontaneity. “Schematizing is indeed a secret, but not the deepest secret of imagination,” – writes Deleuze. Some questions arise at this point. The first one – who speaks here: Kant or Deleuze? The second one – what is this deepest secret of imagination, as an intrigue of this kantian-deleuzean voice? How many possible answers to this question one can discern passing from “early Deleuze” to “late Deleuze”? In this article the author discoved some possible metamorphosis or twists of imagination in the experimental reading of Deleuze. It starts from the submissive position being directed by Understanding or Reason, to the free accord of three independent faculties, towards their discord, even fight, even death of the imagination for the sake of the thought and at least – the whirl closes and comes to the same point but from a different point of view: imagination, together with understanding and reason participate as an integral part of philosophical taste in later Deleuze. But one point united all these different adventures of imagination. Imagination always acts only in relation to the understanding and reason, it never plays free. It could never be able to play alone. Keywords: Kant, Deleuze, imagination.